2019
DOI: 10.2174/0929867325666181115111040
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Components of Brassica Vegetables Including Turnip and the Influence of Processing and Storage on their Anti-oxidative Properties

Abstract: Brassica vegetables, particularly turnip, contain many natural antioxidants. This review focuses on antioxidant components and the influence of different processing and storage conditions on antioxidant activities of some Brassica vegetables including turnip. Long storage times had an adverse effect on antioxidant value of turnip. Also, the activity of antioxidants in cruciferous vegetables could be influenced by antioxidant breakdown and leaching during cooking. Heat treatment has a major impact on the antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…It will be needed to test dietary differences between low and highrate countries. Foods with potent antioxidant or anti ACE activity-like uncooked or fermented cabbage [28][29][30]are largely consumed in low-death rate European countries, Korea and Taiwan, and might be considered in the low prevalence of deaths.…”
Section: Possible Interactions Between Diet and Covid-19 Death Ratementioning
confidence: 99%
“…It will be needed to test dietary differences between low and highrate countries. Foods with potent antioxidant or anti ACE activity-like uncooked or fermented cabbage [28][29][30]are largely consumed in low-death rate European countries, Korea and Taiwan, and might be considered in the low prevalence of deaths.…”
Section: Possible Interactions Between Diet and Covid-19 Death Ratementioning
confidence: 99%
“…Bioavailability of the nutraceuticals is affected by their physicochemical characteristics, such as the physical state, the chemical structure, the solubility, the lipophilicity, and so forth. Most nutraceuticals are extracted from the natural plant sources and are presented as the crystalline or amorphous powders with high melting points and different water solubilities (Gharehbeglou & Jafari, 2019; Mahdavi, Jafari, Ghorbani, & Assadpoor, 2014; Taghvaei & Jafari, 2015). Other nutraceuticals such as CLAs and ω‐3/ω‐6 PUFAs are liquid, lipophilic, and water‐insoluble substances (Mehrad, Shabanpour, Jafari, & Pourashouri, 2015; Pourashouri et al., 2014).…”
Section: External Factors Affecting the Nutraceutical Bioavailabilitymentioning
confidence: 99%
“…Food processing affects the bioaccessibility and bioavailability of nutraceuticals differently. Research has shown that the impact of processing on the bioaccessibility and bioavailability of nutraceuticals is dependent on the type of nutraceuticals, the structure and composition of the food matrix as well as the processing technique (Evrendilek, 2018; Gharehbeglou & Jafari, 2019). For example, chopping plant‐based foods (vegetables, fruits, seeds, nuts, and berries) can improve the nutraceutical bioavailability by breaking the cell walls of chloroplasts or chromoplasts making the nutraceutical more accessible (Quiros‐Sauceda et al., 2017).…”
Section: External Factors Affecting the Nutraceutical Bioavailabilitymentioning
confidence: 99%
“…ACE2 serves as a SARS-CoV-2 receptor, and the binding of SARS-CoV-2 to ACE2 results in oxidative stress (Ji et al, 2020). Components in fermented cabbages and milk products have potent antioxidant and anti-ACE activity (Ahtesh et al, 2018;Dang et al, 2019;Gharehbeglou and Jafari, 2019). A recent study examined the daily spice consumption per capita across 163 countries affected with COVID-19 and observed a correlation between COVID-19 cases per million population tested and spice consumption per capita per day (Elsayed and Khan, 2020).…”
Section: Bioactive Components Of Spices Against Sars-cov-2-induced Hyperinflammationmentioning
confidence: 99%